Revised stratigraphy of Neogene strata in the Cocinetas Basin, La Guajira, Colombia (2015)
The Cocinetas Basin of Colombia provides a valuable window into the geological and paleontological history of northern South America during the Neogene. Two major findings provide new insights into the Neogene history of this Cocinetas Basin: (1) a formal re-description of the Jimol and Castilletes formations, including a revised contact; and (2) the description of a new lithostratigraphic unit, the Ware Formation (Late Pliocene). We conducted extensive fieldwork to develop a basin-scale stratigraphy, made exhaustive paleontological collections, and performed 87Sr/86Sr geochronology to document the transition from the fully marine environment of the Jimol Formation (ca. 17.9–16.7 Ma) to the fluvio-deltaic environment of the Castilletes (ca. 16.7–14.2 Ma) and Ware (ca. 3.5–2.8 Ma) formations. We also describe evidence for short-term periodic changes in depositional environments in the Jimol and Castilletes formations. The marine invertebrate fauna of the Jimol and Castilletes formations are among the richest yet recorded from Colombia during the Neogene. The Castilletes and Ware formations have also yielded diverse and biogeographically significant fossil vertebrate assemblages. The revised lithostratigraphy and chronostratigraphy presented here provides the necessary background information to explore the complete evolutionary and biogeographic significance of the excellent fossil record of the Cocinetas Basin.